The impact of petroleum prices on vegetable oils prices: evidence from co-integration tests - Abdel Hameed, Amna Awad; Mohamed Arshad, Fatimah (Malaysian Palm Oil Board, 2009)
The prices of petroleum and vegetable oils appear to be moving in tandem, a trend which was not observed before. This study seeks to investigate the long-term relationship between the prices of crude oil and selected vegetable oils. To that end, the bivariate co-integration approach using the Engle-Granger two-stage estimation procedure was applied. The study utilized monthly data over the period of January 1983 through March 2008. The results provide strong evidence of a long-run relationship between the two product prices.